2013
DOI: 10.1080/09712119.2012.739092
|View full text |Cite
|
Sign up to set email alerts
|

Effect of probiotics supplementation in diets with different nutrient densities on growth performance, nutrient digestibility, blood characteristics, faecal microbial population and faecal noxious gas content in growing pigs

Abstract: A total of 144 pigs with initial BW of 29.4890.58 kg were used in a 6-wk experiment to evaluate the probiotics supplementation (Enterococcis faecium, 1.0 )10 10 CFU/g) with different nutrient densities in growing pigs. Pigs were randomly allotted to one of four treatments in a 2 )2 factorial arrangement of treatments with two levels of nutrient density and probiotic (0 or 0.1%) according to their sex and BW (nine replicate pens with two gilts and two barrows per pen). Pigs fed the higher nutrient density diets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
48
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 19 publications
19
48
1
Order By: Relevance
“…1 Faecal score 1-5, in which 1 = hard, dry pellets in a small, hard mass; 2 = hard, formed stool that remains firm and soft; 3 = soft, formed, and moist stool that retains its shape; 4 = soft, unformed stool that assumes the shape of the container; 5 = watery, liquid stool that can be poured (Lan et al, 2016) Furthermore, the dietary treatments did not affect faecal score in pigs. In agreement with the current study, Yan and Kim (2013) and Lan et al (2016) reported that faecal Lactobacillus increased by probiotics supplementation. However, Lan et al (2016) observed a reduction in faecal E. Coli in weaning pigs fed probiotic blend.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…1 Faecal score 1-5, in which 1 = hard, dry pellets in a small, hard mass; 2 = hard, formed stool that remains firm and soft; 3 = soft, formed, and moist stool that retains its shape; 4 = soft, unformed stool that assumes the shape of the container; 5 = watery, liquid stool that can be poured (Lan et al, 2016) Furthermore, the dietary treatments did not affect faecal score in pigs. In agreement with the current study, Yan and Kim (2013) and Lan et al (2016) reported that faecal Lactobacillus increased by probiotics supplementation. However, Lan et al (2016) observed a reduction in faecal E. Coli in weaning pigs fed probiotic blend.…”
Section: Resultssupporting
confidence: 81%
“…Chen et al (2005) suggested that average bodyweight gain was significantly improved by the addition of probiotics in growing pigs when fed 0.2% of probiotic blend in diet. According to the authors' research findings, Alexopoulos et al (2004) and, more recently, Ross et al (2010) and Yan & Kim (2013) found that dietary probiotics inclusion led to a higher ADG, ADFI, and FCR than in pigs fed no probiotics. As a result, the same authors suggested that the current probiotic blend has the potential to improve productive performance of growing-finishing pigs probably because of increased nutrient digestibility.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Inclusion of Enterococcus faecium (10 8 CFU/g) significantly improved growth and feed conversion ratio in weanling pigs (Malloa et al 2010). Our previous studies have confirmed that the efficacy of probiotics in pigs was influenced by dietary energy and nutrient density Yan and Kim 2013).…”
supporting
confidence: 48%
“…Recently increased focus on environment pollution has led to the requirement of reducing nitrogen excretion by farm animals (Chu et al 2013;Yan & Kim 2013). It has been well accepted that the use of crystalline amino acids (AA) in low crude protein (CP) diets can reduce the nitrogen excretion in swine manure by more than 35% (Le et al 2006;Nyachoti et al 2006).…”
Section: Introductionmentioning
confidence: 99%